Parameterized approximation of dominating set problems - Downey, Rodney G.; Fellows, Michael R.; McCartin, Catherine; Rosamond, Frances (Information processing letters, 2008)
A problem open for many years is whether there is an FPT algorithm that given a graph G and parameter k, either: (1) determines that G has no k- Dominating Set, or (2) produces a dominating set of size at most g ( k ) , where g ( k ) is some fixed function of k. Such an outcome is termed an FPT approximation algorithm. We describe some results that begin to provide some answers. We show that there is no such FPT algorithm for g ( k ) of the form k + c (where c is a fixed constant, termed an additive FPT approximation), unless FPT = W [ 2 ] . We answer the analogous problem completely for the related Independent Dominating Set (IDS) problem, showing that IDS does not admit an FPT approximation algorithm, for any g ( k ) , unless FPT = W [ 2 ] .